Video Game sebagai Media Sosialisasi Politik: Satu Telaah - Arditya Prayogi; Nurifah Mumtazah; Salwa Salwa; Chomsah Rachmawati; Zahra Khoirunnisa; Riki Nasrullah; Imam Prayogo Pujiono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The development of digital technology has positioned video games beyond mere entertainment to become a cultural medium with the potential to influence players' social and political perspectives. In this context, video games are seen as relevant as a medium for political socialization because they present interactive narratives, moral choices, and social simulations that allow players to directly experience dilemmas of power, justice, responsibility, and state-citizen relations. This article aims to analyze the potential of video games as a medium for political socialization, examine narrative elements that influence the formation of political awareness, and examine the possibility of integrating the Indonesian socio-cultural context into game narratives. This research uses a qualitative approach with a literature review design through a search of various literature sources. The results indicate that video games can serve as a medium for informal political socialization through participatory experiences, moral reflection, and the immersive internalization of political values. This potential will be further enhanced by incorporating local Indonesian contexts, such as mutual cooperation (gotong royong), diversity, and social justice. This study confirms that video games are worthy of being positioned as an educational-cultural medium that can expand political education models in the digital era.